Comparison of surgical condition in endoscopic sinus surgery using remifentanil combined with propofol, sevoflurane, or desflurane - Yoo, Hyung-Seok; Han, Jin Hee; Park, Sung Wook; Kim, Keon Sik (Korean journal of anesthesiology, 2010)
Various maneuvers are commonly used to achieve the ideal operative field necessary for successful endoscopic sinus surgery (ESS). There are a few contradictory reports on this subject and the consensus is that propofol anesthesia results in a better or similar surgical field and less or similar amount of bleeding than volatile anesthesia. The aim of this study was to compare the surgical field in patients in whom intravenous anesthesia is used as opposed to balanced general anesthesia. SIXTY PATIENTS UNDERGOING ESS WERE RANDOMLY ASSIGNED INTO THREE GROUPS, EACH OF WHICH USED A DIFFERENT TYPE OF ANESTHESIA: propofol/remifentanil (PRO/REM) group, sevoflurane/remifentanil (SEV/REM) group, and desflurane/remifentanil (DES/REM) group. We aimed to maintain the intraoperative mean blood pressure (MBP) at 65 mmHg and the heartrate (HR) at about 75 beats per minute. The quality of visibility of the surgical field was graded, using a validated scoring system, 60 minutes after the start of the operation. All groups had a similar MBP and mean HR at 60 minutes after the operation started. There was no significant differences among the three groups for surgical grade score (P = 0.83). In this comparative study of three anesthetic combinations (PRO/REM, SEV/REM, and DES/REM) in patients undergoing ESS with controlled BP and HR, we did not observe any significant differences in the surgical grade scores.